The Combined Effect of Aging and Performance Level on Pacing in Duathlon – the “ITU Powerman Long Distance Duathlon World Championships” - Nikolaidis, Pantelis T.; Chtourou, Hamdi; Ramirez-Campillo, Rodrigo; Villiger, Elias; Rosemann, Thomas; Knechtle, Beat (Frontiers in Psychology, 2019)
The role of age and performance level has been investigated in runners such as marathoners, but not in multi-sports athletes such as duathletes (running, cycling, and running). Thus, the aim of the present study was to examine the combined effects of aging and performance level on pacing of duathletes competing in two different race distances. Pacing (defined as the relative contribution of cycling time, %, to the overall race time) was analyzed for 6,671 duathletes competing from 2003 to 2017 in the short distance race (10 km first run, 50 km cycling and 5 km second run) or long distance race (10 km first run, 150 km cycling and 30 km second run) of ‘Powerman Zofingen’, the ‘ITU Powerman Long Distance Duathlon World Championships’. Men were faster, older, and spent less time (%) in cycling than women in both distances races (p<0.001). Younger age groups spent more time (%) in cycling than their older counterparts in women (both short and long distance, p=0.036, ηp2=0.031, p=0.025, ηp2=0.044, respectively) and men (long distance race, p<0.001, ηp2=0.016). Fast performance groups spent more time (%) in cycling than their slower counterparts in short (women, p<0.001, ηp2=0.057; men, p<0.001, ηp2=0.035) and long distance (women, p<0.001, ηp2=0.070; men, p<0.001, ηp2=0.052). A small age group×performance group interaction on cycling time (%) was observed in the men’s short distance (p=0.001, ηp2=0.020) - but not in the long distance or in women - with smaller differences between performance groups in the older than in the younger age groups. Women, young and fast duathletes were relatively slower in cycling than men, old and slow duathletes; that was, old duathletes were relatively faster in cycling than in running. Moreover, there was indication that the difference in pacing among performance groups might be attenuated with aging. Since fast duathletes were relatively faster in running than in cycling, slow duathletes should be encouraged to cycle slower and run faster.